Pandemia como guerra civil: o paradigma biopolítico e o caso brasileiro na leitura de Giorgio Agamben - LIMA, Giovanna Faciola Brandão de Souza (Universidade Federal do Pará, 2023)
This dissertation aims to analyze the coronavirus pandemic as corresponding to the civil war in the way that the Italian author, Giorgio Agamben, understands this phenomenon, that is, as a biopolitical paradigm. It is an explanatory research of the bibliographic type, but its method is the same used by the philosopher: the paradigmatic method. The main theoretical reference of this research is the Italian philosopher Giorgio Agamben, especially with regard to his notion of civil war as a paradigm and the concepts of biopolitics, sovereignty, bare life and his warnings about the coronavirus pandemic. Michel Foucault's writings were also used as a theoretical basis for this research, precisely with regard to the courses in which he develops his notion of biopolitics, biopower and the security society. Motivated by the philosophical discussion triggered by Agamben's texts on COVID-19, the guiding problem of this dissertation is the following: to what extent can the policies to combat COVID 19 in Brazil be thought of as civil war as a biopolitical paradigm? From the study of Giorgio Agamben's theory, it was possible to understand that civil war as a paradigm is not about a warlike conflict or between States, but a device of control and surveillance of the population and that it represents the threshold in which the non-political becomes politicizes and the politician saves himself. And the interlocutions with the thought of Michel Foucault revealed that this was only possible from the taking of life by power through a series of techniques that affect all spheres of the individual. Security reasons, in this context, in the wake of Foucault's investigations and Agambenian warnings, assumed a fundamental role as a justification for the adoption of permanent exceptional measures, not only in the name of preserving individuals, but also to establish a state of insecurity widespread in order to keep citizens always in combat. In this sense, it was possible to identify that the form that the civil war has taken today is the coronavirus pandemic, manifesting itself in the form of terror in a way that anyone can be considered a source of contagion. Finally, we identified that in Brazil the measures to combat the virus can be interpreted as civil war, as a device to control the lives of citizens, at the same time that the government adopted a kind of death policy in the name of the uninterrupted functioning of the market and the capital.